Bioactive exopolysaccharide-composites based on gold and silver nanoparticles tailored for wound healing. (March 2023) - Concórdio-Reis, Patrícia; Ramos, Kleyde; Macedo, Ana Catarina; Serra, Ana Teresa; Moppert, Xavier; Guézennec, Jean; Sevrin, Chantal; Grandfils, Christian; Reis, Maria A.M.; Freitas, Filomena
Abstract: The marine isolate Alteromonas macleodii Mo 169 secretes a exopolysaccharide (EPS) mainly composed of glucuronic acid and containing sulphate, pyruvate, and lactate as acyl substituents. The high density of negatively charged functional groups of the EPS renders it the ability to function as a stabilizing and reducing agent for the synthesis of metallic nanoparticles (NP). In this study, silver and gold NP (AgNP and AuNP, respectively) were successfully synthesized and stabilized by A. macleodii Mo 169 EPS. The obtained AuNP and AgNP presenting a spherical shape with an average particle size of 16 and 15 nm, respectively, displaying a polysaccharide layer that apparently contributed to reduce their aggregation. The cytotoxicity of the EPS and the bio-nanocomposites was evaluated on human keratinocyte (HaCaT) and fibroblast (CCD-1079Sk) cell lines. None of the samples demonstrated cytotoxicity for concentrations up to 1000 mg L −1 . In vitro wound healing experiments demonstrated that both bio-nanocomposites promoted cell migration for concentrations above 100 mg L −1, thus contributing for a faster wound recovery. These findings demonstrate for the first time the potential of A. macleodii Mo169 EPS to synthesize and stabilize nanoparticles that possess promising physical-chemical and biological characteristics that render them valuable for the development of novel biomaterials for several applications, including wound care. Graphical Abstract: ga1 Highlights: Green synthesis of gold and silver nanoparticles (AuNP and AgNP, respectively). Alteromonas macleodii Mo 169 exopolysaccharide was used as reducer and stabilizer. The synthesized nanoparticles were spherical, stable and homogenous in size. The bio-nanocomposites did not show cytotoxicity for the concentration range tested. In vitro studies showed that the bio-nanocomposites had wound healing potential.